Supply chain transparency: Consumer reactions to incongruent signals - Mollenkopf, Diane A.; Peinkofer, Simone T.; Chu, Yu ( Jade) (Journal of Operations Management, 2022)
AbstractIn response to consumers' growing interest in how products are sourced, produced, and distributed, organizations are increasingly transparent about their supply chain sustainability practices. Supply chain transparency (SCT) efforts are intended to signal positive information about the company to consumers but the benefits are often unclear, especially when consumers receive multiple, but mixed signals that include negative events. We draw on signaling theory to explore how consumers develop impressions of a company's products based on different evaluative dimensions: the positive integrity signal of SCT and the negative capability signal of a product recall. The incongruent signal set creates ambiguity for consumers in assessing product quality and subsequent purchase decisions. We develop two scenario‐based experiments to test aspects of interdimensional signal incongruence. Experiment 1 investigates the magnitude of signal incongruity by considering combinations of different levels of SCT and product recall severity. Experiment 2 investigates the temporal effect of the incongruent signals, considering the restorative effect of SCT after a product recall signal has been received. While product recall signals are salient for consumers in shaping perceptions of product quality and purchase intentions across both experiments, we demonstrate the strategic value of SCT as a positive integrity signal to consumers.